Influence of Religion on Pro-Environmental Behavior: A Systematic Literature Review - Shrestha, Richan (Journal of religion and health, 2025)
Religion is one of the major factors influencing pro-environmental behavior (PEB) to mitigate the climate crisis. However, previous studies have not provided a conclusive answer on how religion influences PEB. Additionally, it is crucial to consolidate a comprehensive understanding of trends and the influence of religion on PEB. Thus, the main objectives of this study are to find research trends regarding the relationship between religion and PEB and how religion affects PEB by using a systematic review process. The findings of this study suggest that the research design is predominantly driven by quantitative methodology, with the theory of planned behavior and the theory of reasoned action being the most commonly used frameworks. This study also found that most studies had the direct and indirect (moderating and mediating) influence of religion on PEB. Religion being a significant factor, it should therefore be considered crucial to integrate religious studies into the enviormental studies curriculum. It is also necessary to analyze diverse factors alongside religion for a proper understanding of PEB. This study is helpful for education policymakers, schools, and future researchers.